Literature in our lives talking about texts from Shakespeare to Philip Pullman - Jacobs, Richard 1952- (Routledge, 2020)
This book recreates in written form seventeen of the most popular, frankly personal and engaging lectures on literature given by the award-winning teacher Richard Jacobs, who has been working with students for over forty years. This is a book written for students, whether starting their studies or more experienced, and also for all lovers of literature. At its heart is the conviction that reading, thinking about, and writing or talking about literature involves us all personally: texts talk to us intimately and urgently, inviting us to talk back, intervening in and changing our lives. These lectures discuss, in an open but richly informed way, a wide range of texts that are regularly studied and enjoyed. They model what it means to be excited about reading and studying literature, and how the study of literature can be life-changing - perhaps even with the effect of changing the lives of readers of this eloquent and remarkable book